IDENTIFIKASI DAN PENETAPAN KADAR RHODAMIN B DALAM KERUPUK BERWARNA MERAH YANG BEREDAR DI PASAR ANTASARI KOTA BANJARMASIN - Eka Kumalasari (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Crackers are made from tapioca flour batter mixed with flavorings and colorings, still many outstanding crackers that contain ingredients banned dye Rhodamine B. Rhodamine B is a chemical used for red dye in the textile industry and plastic. Rhodamine B can cause cancer, poisoning, lung irritation, sore eyes, and sore throat. This study aims to identify and determination the levels of Rhodamine B in circulating red crackers Antasari market Banjarmasin.The population is that sold in the red crackers that sold in Antasari market Banjarmasin.. The sampling is technique incidental sampling , that is based on chance, so any population by chance met with researchers can be used as a sample. Identification of Rhodamine B was done by Thin Layer Chromatography (TLC) by using the stationary phase silica GF 254 and mobile phase is elution solvent is n-butanol, ethyl acetate, ammonia (10:4:5). Then detected with a UV lamp 254 nm and 366 nm. While for the determination of levels using Vis spectrophotometry at a wavelength of 544 nm.The results showed that the samples of 6 found one sample containing Rhodamine B, namely samples 5 (cassava crackers matches) and obtained values of 7,25 ± 3,8640 levels mg / kg. Based on these results, Rhodamine B still found in crackers that sold in the market Antasari Banjarmasin.